2002
DOI: 10.1177/0886260502017008001
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Experience and Accuracy in Psychological Profiling of a Violent Crime

Abstract: Although psychological profiling has achieved wide acceptance in law enforcement investigations, there has been little empirical research into the skills required for profiling. One attribute that is frequently cited as quintessential for effective profiling is experience in police investigations. In a study similar in design to Kocsis, Irwin, Hayes, and Nunn, this study examined the importance in profiling of investigative experience by testing groups of homicide detectives, senior police detectives, trainee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 10 publications
(22 reference statements)
8
63
0
1
Order By: Relevance
“…Indeed, excluding that sub-section of the profile, the overall profile accuracy score increases to 49%. Previous research involving students has reported profile accuracy levels of 40% (Kocsis et al, 2000), 41% (Kocsis et al, 2002), and 59% (Kocsis, 2004). 1 Thus, while the current group of students exhibited slightly lower levels of overall profile accuracy compared to the previous groups, they are comparable to the students that were examined in two of Kocsis' studies.…”
Section: Are Students Effective Profilers?supporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, excluding that sub-section of the profile, the overall profile accuracy score increases to 49%. Previous research involving students has reported profile accuracy levels of 40% (Kocsis et al, 2000), 41% (Kocsis et al, 2002), and 59% (Kocsis, 2004). 1 Thus, while the current group of students exhibited slightly lower levels of overall profile accuracy compared to the previous groups, they are comparable to the students that were examined in two of Kocsis' studies.…”
Section: Are Students Effective Profilers?supporting
confidence: 62%
“…Kocsis, 2003aKocsis, ,b, 2004Kocsis, Hayes, & Irwin, 2002;Kocsis, Irwin, Hayes, & Nunn, 2000). The studies emerging from this research program have been interpreted as providing support for some of the profiling skills put forward by Hazelwood et al, particularly logical reasoning ability and an appreciation for the criminal mind (see Kocsis, 2003a for a review of this evidence).…”
Section: Introductionmentioning
confidence: 92%
“…Domain-specifi c knowledge based on probabilities is necessary. Detectives seem to lack the necessary skills to infer characteristics of the offender (Adhami & Browne, 1996;Jackson et al 1997;Kocsis, Hayes, & Irwin, 2002;Kocsis, Irwin, Hayes, & Nunn, 2000). In addition, to infer characteristics without empirical support is currently being criticised (Snook, Cullen, Benell, Taylor, & Gendreau, 2008).…”
Section: Practical Valuementioning
confidence: 95%
“…What emerged as a major study into the evaluation of profiling accuracy was a study by Kocsis (2003). This study undertook an integrated analysis of the data collected in Kocsis et al (2000), Kocsis et al (2002) and Kocsis (2004), in addition to incorporating some additional original data. The findings of Kocsis (2003) revealed a pattern in the capabilities of profilers to surpass all other tested groups in the profiling experiments.…”
Section: The Conflict Of the Meta-analysis Studiesmentioning
confidence: 99%
“…Some evidence emerged in terms of a tentative pattern of profilers surpassing the other sampled groups. Thereafter, Kocsis, Hayes, and Irwin (2002) used the previous murder case but focused on examining the value that experience in criminal investigation may have on the process of proficient profiling. This study failed to find evidence to support the need for investigative experience in proficient profiling.…”
Section: The Quasi-experimental Studies Of Profiling Performancementioning
confidence: 99%